Menjamak Sholat Bagi Pengantin yang Melaksanakan Walimah Al ’Urs Perspektif Syekh Alwi Ahmad Saqqaf dan Imam Asy-Syaukani - Mayunda, Usdha Lifa; Marpaung, Aripin (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
In the current era of progress, the wedding party (walimah al 'urs) is considered by some people as something that must be fulfilled when someone is married. Its raelitas can be seen when there is a wedding party (walimah al 'urs), some of the bride and groom will leave the prayer, some of them do their obligations after the prayer time is over and some of them choose plural. In this case the author takes the strongest opinion after munaqasyah al-adillah, namely the opinion of Sheikh Alwi Ahmad Saqqaf. The aim of this study is to examine further the Multiple Prayers for Wedding Brides When Carrying Out Walimah Al'urs from the Perspective of Sheikh Alwi Ahmad Saqqaf and Imam Asy-Syaukani. The research method used is normative sociological research method, which is comparative. The results of the study show that there are multiple prayers for the bride and groom when carrying out a wedding party (walimah al 'urs), so some scholars allow it and some do not. Among these opinions is the opinion of Sheikh Alwi Ahmad Saqqaf that it is permissible to pray multiple prayers when there is a need or an excuse. Meanwhile, another opinion is the opinion of Imam Asy-Syaukani that it is permissible to pray together only because of rain, fear and illness. So the most relevant relation to the existing case chronology is the opinion of Sheikh Alwi Ahma Saqqof. Namely those who say it is permissible to make plural taqdim absolutely other than because of traveling, illness, and for other than the two of other reasons.